2020
DOI: 10.1126/scitranslmed.aax2879
|View full text |Cite
|
Sign up to set email alerts
|

BET inhibition increases βIII-tubulin expression and sensitizes metastatic breast cancer in the brain to vinorelbine

Abstract: Metastases from primary breast cancer result in poor survival. βIII-tubulin (TUBB3) has been established as a therapeutic target for breast cancer metastases specifically to the brain. In this study, we conducted a systematic analysis to determine the regulation of TUBB3 expression in breast cancer metastases to the brain and strategically target these metastases using vinorelbine (VRB), a drug approved by the U.S. Food and Drug Administration (FDA). We found that human epidermal growth factor receptor 2 (HER2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Some genes in our prognostic signature model have been clarified to be involved in the progression of various tumors, including FGL1 (fibrinogen-like protein 1), TUBB3 (tubulin beta 3), TNIP1 (TNF-α-induced protein 3-interacting protein 1), CALD1 (caldesmon 1), ARPP19 (cAMP-regulated phosphoproteins 19), FCGRT (Fc fragment of IgG receptor and transporter), ANKDD1A (ankyrin repeat and death domain containing 1A) and SMARCC2 (SWI/SNF related, matrix associated, actin dependent regulator of chromatin subfamily C member 2) (Wang et al 2019 ; Kanojia et al 2020 ; Yang et al 2019b ; Liu et al 2018 ; Ye et al 2020 ; Xue et al 2020 ; Feng et al 2018 ; Yuan et al 2018 ). Among these survival-related genes, FGL1 and ANKDD1A were intriguingly closely associated with the tumor microenvironment and immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Some genes in our prognostic signature model have been clarified to be involved in the progression of various tumors, including FGL1 (fibrinogen-like protein 1), TUBB3 (tubulin beta 3), TNIP1 (TNF-α-induced protein 3-interacting protein 1), CALD1 (caldesmon 1), ARPP19 (cAMP-regulated phosphoproteins 19), FCGRT (Fc fragment of IgG receptor and transporter), ANKDD1A (ankyrin repeat and death domain containing 1A) and SMARCC2 (SWI/SNF related, matrix associated, actin dependent regulator of chromatin subfamily C member 2) (Wang et al 2019 ; Kanojia et al 2020 ; Yang et al 2019b ; Liu et al 2018 ; Ye et al 2020 ; Xue et al 2020 ; Feng et al 2018 ; Yuan et al 2018 ). Among these survival-related genes, FGL1 and ANKDD1A were intriguingly closely associated with the tumor microenvironment and immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of brain metastases is 30-55% in patients with HER2 positive breast cancers. Brain-predominant genes critical for the establishment of HER2 positive breast cancer brain metastases include a cytoskeletal protein βIII-tubulin (encoded by TUBB3 gene) [85] and the fatty acid-binding protein 7 (encoded by FABP7 gene) [86]. FABP7, a brain-specific intracellular lipid-binding protein, regulates fatty acid uptake and intracellular lipid droplet formation.…”
Section: Metabolic Network In Her2 Positive Breast Cancermentioning
confidence: 99%
“…Recent work has identified that MZF1 is able to bind to the TUBB3 loci, with three potential sites predicted up to 600 base pairs upstream of the first exon of TUBB3 transcript variant 2 ( Kanojia et al, 2020 ). The ability of MZF1 to bind to the TUBB3 loci was identified while looking for means to upregulate βIII-tubulin expression in HER2 positive breast cancer in an effort to induce sensitivity to the TBA, vinorelbine ( Kanojia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has identified that MZF1 is able to bind to the TUBB3 loci, with three potential sites predicted up to 600 base pairs upstream of the first exon of TUBB3 transcript variant 2 ( Kanojia et al, 2020 ). The ability of MZF1 to bind to the TUBB3 loci was identified while looking for means to upregulate βIII-tubulin expression in HER2 positive breast cancer in an effort to induce sensitivity to the TBA, vinorelbine ( Kanojia et al, 2020 ). Building on previous work that identified TUBB3 expression to be modulated by the members of the Bromdodmain and Extraterminal (BET) protein family ( Piunti et al, 2017 ), Kanojia et al (2020) identified increased TUBB3 /βIII-tubulin expression in response to BET inhibition which led to increased sensitivity to Vinorelbine both in vitro and in vivo ( Kanojia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation